Automated 3D assembly of periodic alumina‐epoxy composite structures. Issue 9 (20th April 2018) - Biggemann, Jonas; Diepold, Benedikt; Pezoldt, Marc; Stumpf, Martin; Greil, Peter; Fey, Tobias
Abstract: Modular composites with a 3D periodic structure, consisting of a major brittle inorganic phase (building blocks) and a minor viscoelastic organic matrix, offer great potentials for improved fracture toughness and failure probability in polymer‐ceramic composites. Alumina building blocks with dimensions of 1500 μm were assembled by a novel placing system equipped with an automatic optical inspection (AOI) system. The AOI system coupled with shape recognition enables simultaneous dimensional characterization, tolerance sorting, and flexible placing of different shaped building blocks. 3D periodic structures with cubic, monoclinic, and triclinic unit cells were fabricated by high accuracy placing of cubic building blocks enabling near‐net shape manufacturing. The placing precision of the assembled structures was determined by μCT to have a maximum deviation of ±78 μm. The structures were afterward infiltrated with a soft epoxy resin to fabricate epoxy‐alumina composites. The brick‐and‐mortar like building block arrangements of the monoclinic and triclinic structures exhibited improved bending strength, fracture toughness, and failure probability compared to monolithic epoxy, due to crack deflection and pull‐out toughening mechanisms. A maximum bending strength of 35.1 ± 7.5 MPa, a work‐of‐fracture of 814.7 ± 255.1 J/m² and a calculated fracture toughness of 4.8 ± 0.8 MPa m for the triclinic structures was achieved.